Gestión de créditos y cobranzas y sus efectos en los estados financieros en el Comercial Bellnovainser de la ciudad de Babahoyo, en el periodo 2020-2021. - Onofre Bravo, Quino Johan (2022)
The objective of this Curriculum Integration Work is to analyze the management of credits and collections and their effects on the financial statements of the Bellnovainser commercial for the 2020-2021 period. It is carried out in the city of Babahoyo where the Bellnovaincer commercial is established, in Av. General Barona Between May 27 and Pedro Carbo, the commercial is dedicated to the sale of technological items, appliances and more, among other things for the home, considering the information presented, the situation of the commercial is analyzed, helping to determine the margin exact profitability generated by the company in its credit management and collection activities. For a growing company such as Comercial Bellnovaincer, it is necessary to apply current regulations in this way to proceed with the analysis of credit and collection management and its effects on the financial statements to know the indicators of effectiveness, liquidity, indebtedness and profitability of the company. As a research methodology, two types of research are used in order to carry out successful work: First, the type of exploratory research that is used when the objective of making a first approximation to an unknown matter or about which has not been investigated enough. Second, the type of theoretical research used is aimed at generating knowledge, regardless of its practical application. In this case, data collection is used to generate new general concepts. This led to the analysis and reflection of how important an adequate management of credits and collections becomes and its effects on the financial statements.